Necrostatin-1 Synergizes the Pan Caspase Inhibitor to Attenuate Lung Injury Induced by Ischemia Reperfusion in Rats. (24th October 2020) - Wang, Liangrong; Chen, Baihui; Xiong, Xiangqing; Chen, Shunli; Jin, Lida; Zhu, Meizhen
Abstract : Background . Both apoptosis and necroptosis have been recognized to be involved in ischemia reperfusion-induced lung injury. We aimed to compare the efficacies of therapies targeting necroptosis and apoptosis and to determine if there is a synergistic effect between the two therapies in reducing lung ischemia reperfusion injury. Methods . Forty Sprague-Dawley rats were randomized into 5 groups: sham (SM) group, ischemia reperfusion (IR) group, necrostatin-1+ischemia reperfusion (NI) group, carbobenzoxy-Val-Ala-Asp-fluoromethylketone+ischemia reperfusion (ZI) group, and necrostatin-1+carbobenzoxy-Val-Ala-Asp-fluoromethylketone+ischemia reperfusion (NZ) group. The left lung hilum was exposed without being clamped in rats from the SM group, whereas the rats were subjected to lung ischemia reperfusion by clamping the left lung hilum for 1 hour, followed by reperfusion for 3 hours in the IR group. 1 mg/kg necrostatin-1 (Nec-1: a specific necroptosis inhibitor) and 3 mg/kg carbobenzoxy-Val-Ala-Asp-fluoromethylketone (z-VAD-fmk: a pan caspase inhibitor) were intraperitoneally administrated prior to ischemia in NI and ZI groups, respectively, and the rats received combined administration of Nec-1 and z-VAD-fmk in the NZ group. Upon reperfusion, expressions of receptor-interacting protein 1 (RIP1), receptor-interacting protein 3 (RIP3), and caspase-8 were measured, and the flow cytometry analysis was used to assess the cell death patterns in the lung tissue. Moreover, inflammatory marker levels in the bronchoalveolar lavage fluid and pulmonary edema were evaluated. Results . Both Nec-1 and z-VAD-fmk, either alone or in combination, significantly reduced morphological damage, inflammatory markers, and edema in lung tissues following reperfusion, and cotreatment of z-VAD-fmk with Nec-1 produced the optimal effect. The rats treated with Nec-1 had lower levels of inflammatory markers in the bronchoalveolar lavage fluid than those receiving z-VAD-fmk alone (P < 0.05 ). Interestingly, the z-VAD-fmk administration upregulated RIP1 and RIP3 expressions in the lung tissue from the ZI group compared to those in the IR group (P < 0.05 ). Reperfusion significantly increased the percentages of necrotic and apoptotic cells in lung tissue single-cell suspension, which could be decreased by Nec-1 and z-VAD-fmk, respectively (P < 0.05 ). Conclusions . Nec-1 synergizes the pan caspase inhibitor to attenuate lung ischemia reperfusion injury in rats. Our data support the potential use of Nec-1 in lung transplantation-related disorders.